2009
DOI: 10.1007/s12598-009-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

MoSi2 oxidation resistance coatings for Mo5Si3/MoSi2 composites

Abstract: In order to improve the oxidation resistance properties of 30 at.% Mo 5 Si 3 /MoSi 2 composite at high temperature in air, a molybdenum disilicide coating was prepared on its surface by a molten salt technology. XRD and SEM analysis showed that only tetragonal MoSi 2 phase existed in the coating after being siliconized for 5 h at 900°C. The oxidation film formed on the uncoated sample was not dense, so that oxygen diffused easily through it. The volatilization of MoO 3 resulted in the oxidation film separating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In investigations of the last two decades, MoSi 2 and MoSi 2 composites have been used as protective layers to protect ceramic matrix composite (CMC) materials that will be exposed to high temperatures (Ibano et al, 2007;Zhu et al, 2022b;Ren et al, 2022) and corrosive environments, especially in highly oxidizing environments that can embrittle the material (Xu et al, 1999;Zhao et al, 2006;Fu et al, 2009;Sooby Wood et al, 2016;Bezzi et al, 2019;Ren et al, 2020). Most researchers seek for the materials to be protected to not only not rust easily but also have high thermal shock resistance and that a dense protective SiO 2 layer forms at high temperatures to prevent oxidation for as long as possible (Yan et al, 2009;Zhao, 2010;Wang et al, 2017;Yang et al, 2021;Wei et al, 2022).…”
Section: Oxidation Of Mosimentioning
confidence: 99%
“…In investigations of the last two decades, MoSi 2 and MoSi 2 composites have been used as protective layers to protect ceramic matrix composite (CMC) materials that will be exposed to high temperatures (Ibano et al, 2007;Zhu et al, 2022b;Ren et al, 2022) and corrosive environments, especially in highly oxidizing environments that can embrittle the material (Xu et al, 1999;Zhao et al, 2006;Fu et al, 2009;Sooby Wood et al, 2016;Bezzi et al, 2019;Ren et al, 2020). Most researchers seek for the materials to be protected to not only not rust easily but also have high thermal shock resistance and that a dense protective SiO 2 layer forms at high temperatures to prevent oxidation for as long as possible (Yan et al, 2009;Zhao, 2010;Wang et al, 2017;Yang et al, 2021;Wei et al, 2022).…”
Section: Oxidation Of Mosimentioning
confidence: 99%
“…MoSi 2 has been rapidly applied in electronics, metallurgy, nuclear industry, and aerospace fields [3][4][5]. It is widely used in space reactors emitter, missile exhaust nozzle, satellite rocket boosters, engine blades and high-temperature electrodes and other fields [6,7]. At present, the main coating preparation methods of molybdenum and its alloys include hot pressed sintering [8], induction plasma deposition [9], electroless deposition [10], chem ical vapor deposition (CVD) [11], mechanical alloying [12], and self-propagating high-temperature synthesis (SHS) [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the brittleness at ambient temperature (fracture toughness K IC , approximately 2-3 MPa•m 1/2 ) and low strength at high temperature (σ 0.2 , approximately 20 MPa at 1600°C) are still the flaw of MoSi 2 for the most sophisticated applications [2]. According to the previous studies, the mechanical properties of MoSi 2 could be increased by alloying processing or by introducing some reinforcement phase, such as Mo 5 Si 3 [3], ZrO 2 [4], ZrB 2 [5] and SiC [6]. In our previous work [7], it was confirmed that the addition of carbon nanotubes (CNTs) to the MoSi 2 matrix results in the improvement in both hardness and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%